New Material from Galenʼs On the Authentic and Spurious Works of Hippocrates. - Das, Aileen R. (Classical Philology, 2018)
A literary criticism of the book "On the Authentic and Spurious Works of Hippocrates," by Galen is presented. Topics mentioned include the several works of physician Hippocrates that are authentic, according to Galen, including "Epidemics," "Nature of Man," and "Diet in Acute Diseases," the subject matter of Hippocratic treatises, and the contemporary methods in medical training.